WHY THE RICH ARE GETTING RICHER : What Is Financial Education...Really? - Kiyosaki, Robert T., 1947-, author; Wheelwright, Tom, author (Scottsdale, AZ : Plata Publishing)
Kiyosaki believes that our educational system-- and poor job it does on financial education-- is what causes the gap between the rich and everyone else. In this book, he explains why savers are losers, debt and taxes make the rich richer, and why going to school, working hard, getting out of debt, and investing for the long term in the stock market is the worst financial advice for most people. Kiyosaki and Wheelwright share ideas on how to survive-- and thrive-- into the future.